Clinical Pharmacology and Pharmacy of Antimicrobial Agents (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In this Special Issue, our aim was to collect studies on clinical pharmacology and pharmacy of antimicrobial agents from both human and veterinary medicine as the complex problem of AMR requires actions taken within the One Health approach that involve both fields. Studies covered here are about new or optimized usage of already authorized antimicrobials, as well as discoveries about new agents, new combinations of drugs, and drug repositioning. Pharmacodynamic, pharmacokinetic, and toxicological aspects of individual and combinational drug use are areas covered in this Special Issue.